Histological Adaptations of the Retina in the Black Francolin (Francolinus francolinus, Linnaus, 1766) and the Caucasian Squirrel (Sciurus anomalus, Gmelin, 1778) - Abid, Shaimaa A.; Fadhil, Lamyaa Abdulridha; Abdul Wahab, Sura Abdul Munaff (Iraqi Journal of Science, 2026)
Ecological diversity between the diurnal bird of F. francolinus and the diurnal squirrel of S. anomalus reflects the ability to adapt to their vision environments. The histological characteristics of the retina in F. francolinus and S. anomalus were studied using light microscopy. The retina of F. francolinus is avascular, while that of S. anomalus is vascular. The retina in both species consists of ten layers. In both species, the retina includes cones and rods, and the increased cone density is adapted for daytime and color vision. The retina of F. francolinus contains a shallow fovea for visual acuity. This shallow fovea was characterized by the presence of all retinal layers in the pit that provided a monocular view for near-distance sight. The S. anomalus retina was distinguished by the presence of blood vessels extending within the ganglion cell and nerve fiber layers. Thus, visual acuity played an important role in the environment of both F. francolinus and S. anomalus as well as in their behaviors.